2010
DOI: 10.2202/1542-6580.2353
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Newtonian and Gas-Non-Newtonian Slug Flow in Vertical Pipe, Part I: Gas Holdup Characteristics

Abstract: Studies on two-phase gas-liquid co-current flow with non-Newtonian liquid system has attracted the attention of researchers over the years due to its wide-spread applications and importance in various different processes in chemical and biochemical industries, such as the process of two-phase in oil and gas wells, transportation systems of crude and refined products, and food processing in biochemical engineering and bio-reactors. This article examines the sole objective of experimental studies on gas holdup i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The vertical test section is of 19.05 mm internal diameter and 3.4 m length. The flow regime has been described in our earlier studies (Majumder et al, 2010). In the present study air and different types of liquids with their physical properties is shown in Table 1.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…The vertical test section is of 19.05 mm internal diameter and 3.4 m length. The flow regime has been described in our earlier studies (Majumder et al, 2010). In the present study air and different types of liquids with their physical properties is shown in Table 1.…”
Section: Methodsmentioning
confidence: 90%
“…The detail of the schematic diagram of the experimental setup was described in our earlier studies (Majumder et al, 2010). The apparatus consists of different accessories with a test section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…intense mixing, high heat and mass transfer, high residence time of gas etc. It is not yet recommended for industrial applications due to lack of understanding of complex multiphase phenomena like holdup, pressure drop, mixing, and heat transfer phenomena in the downflow system (Majumder et al, 2010). Three-phase pressure drop and holdup are essential elements for the design of process equipments which is the subject of numerous experimental and numerical studies.…”
Section: Introductionmentioning
confidence: 99%
“…To design and control such equipment efficiently, the values of pressure drops and volumetric fractions of phases must be determined (Begovich and Watson, 1978;Kato et al, 1981;Muroyama and Fan, 1985;Fan, 1989;Shah et al, 1982). Few experimental data on two-phase flow have been available in the downflow column (Marchese et al, 1992;Mandal et al, 2004;Majumder et al, 2006Majumder et al, , 2007Majumder et al, , 2010Sivaiah et al, 2010). There is a lack of studies on the phase fraction and pressure drops in this downflow system with gas-liquid-solid system.…”
Section: Introductionmentioning
confidence: 99%